2020
DOI: 10.3389/fped.2020.579364
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following Primary Repair of Non-proximal Hypospadias in Children: A Systematic Review and Meta-Analysis

Abstract: Purpose: The aim of this study was to systematically review the literature on the complications and postoperative outcomes of children with non-proximal hypospadias.Methods: Electronic databases including PubMed, Embase, and Cochrane Library CENTRAL were searched systematically from January 1990 to June 2020 for the literature that reported the postoperative outcomes of patients with non-proximal hypospadias. Non-proximal hypospadias encompassed distal and mid-penile hypospadias.Results: We included 44 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
2
17
1
Order By: Relevance
“…Nevertheless, the complication rates in our study remain far below the average complication rates of non-proximal hypospadias repair in children. In particular, the systematic meta-analysis of published studies of non-proximal hypospadias repair techniques revealed an overall complication rate of approximately 8% (25). Urethrocutaneous fistula was, as expected, the primary complication reported, with an incidence of 4%, followed by meatal stenosis with 2.1% and urethral stricture with 0.8%.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, the complication rates in our study remain far below the average complication rates of non-proximal hypospadias repair in children. In particular, the systematic meta-analysis of published studies of non-proximal hypospadias repair techniques revealed an overall complication rate of approximately 8% (25). Urethrocutaneous fistula was, as expected, the primary complication reported, with an incidence of 4%, followed by meatal stenosis with 2.1% and urethral stricture with 0.8%.…”
Section: Discussionsupporting
confidence: 56%
“…Surgery is the only cure for hypospadias, and the repair of hypospadias aims to create a straight penis, a neourethra with a meatus at the tip of glans, and a normal appearance of a circumcised phallus ( 7 , 8 ). However, long-term follow-up studies have found that adults with hypospadias may have abnormal urethral function, unsatisfactory appearance of the penis, and problems with erection, ejaculation, or sexual intercourse, which often negatively affect their quality of life ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 systematic review and meta-analysis of primary, nonproximal hypospadias repair reported an overall complication rate of 8.0%, with the most common complication being urethrocutaneous fistula. 1 Complications after proximal hypospadias have been reported to occur with greater frequency. Single-center series assessing 2-stage proximal hypospadias repairs demonstrate overall complication rates of 49% and 53%, with median followup times of 31.7 months and 3.8 years, respectively.…”
mentioning
confidence: 99%